2016
DOI: 10.1101/lm.042655.116
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine enhances spontaneous recovery of contextual fear and changes c-fos early gene expression in infralimbic cortex, hippocampus, and amygdala

Abstract: Exposure therapy, which focuses on extinguishing fear-triggering cues and contexts, is widely used to treat post-traumatic stress disorder (PTSD). Yet, PTSD patients who received successful exposure therapy are vulnerable to relapse of fear response after a period of time, a phenomenon known as spontaneous recovery (SR). Increasing evidence suggests ventral hippocampus, basolateral amygdala, and infralimbic cortex may be involved in SR. PTSD patients also show high rates of comorbidity with nicotine dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…Therefore, we recently examined the effects of nicotine on contextual fear extinction. Our results showed that acute nicotine administration impaired encoding and retrieval of contextual fear extinction memories without affecting general freezing behavior measured in a novel context (Kutlu and Gould, 2014; Kutlu et al, in press). In addition, we also found that the impairing effects of acute nicotine on contextual fear extinction require high-affinity α4β2, but not low-affinity α7, nicotinic acetylcholine receptors (nAChRs, Kutlu et al, 2016).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, we recently examined the effects of nicotine on contextual fear extinction. Our results showed that acute nicotine administration impaired encoding and retrieval of contextual fear extinction memories without affecting general freezing behavior measured in a novel context (Kutlu and Gould, 2014; Kutlu et al, in press). In addition, we also found that the impairing effects of acute nicotine on contextual fear extinction require high-affinity α4β2, but not low-affinity α7, nicotinic acetylcholine receptors (nAChRs, Kutlu et al, 2016).…”
Section: Introductionmentioning
confidence: 60%
“…Also following Kutlu et al (2016), 3 mice from the additional withdrawal experiments (1 from 1 d Saline, 1 from 4 d Nicotine, and 1 from 4 d Saline group) were removed from the study because their initial freezing responses were lower than 15% during the retention test. This acquisition criterion, as used in our and others’ previously published work (Kutlu et al, 2016, in press; Corcoran et al, 2005) is essential to any studies that examines extinction behavior. This is because, in the absence of this criterion, it would be impossible to determine if extinction occurs when the initial freezing levels are at baseline levels of freezing.…”
Section: Methodsmentioning
confidence: 99%
“…Kenney et al (2012) also showed that nicotine infusions into the ventral hippocampus impaired contextual fear conditioning. Interestingly, in a recent study, we found that acute nicotine impaired extinction retrieval and this effect was associated with increased c-fos immediate early gene expression in the ventral but not dorsal hippocampus (Kutlu et al, under review). Therefore, it is possible that the high-affinity α4β2 nAChRs in another region within the fear extinction circuitry may primarily control the impairing effects of acute-nicotine on contextual fear extinction.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is not surprising to see a divergence between dHPC and vHPC during contextual fear extinction. In support, we recently showed that acute nicotine-induced impairment of contextual fear extinction resulted in augmented c-fos expression in vHPC but not in dHPC (Kutlu et al, 2016b). Overall, these results suggest that the effects of nicotine on contextual fear extinction may be largely mediated by vHPC.…”
Section: Discussionmentioning
confidence: 70%
“…Second, in order to test our hypothesis that acute nicotine alters memory consolidation processes, we examined the effects of acute nicotine on consolidation of extinction memories by administering nicotine within and outside the memory consolidation window, a 6 hr temporal window where newly acquired memories are stabilized into long-term memory storage (Dudai, 2004; Katche et al, 2013). Given that our previous studies showed that the dorsal hippocampus (dHPC) mainly controlled the effects of nicotine on fear acquisition (Kenney et al, 2010; Gould et al, 2014) whereas the ventral hippocampus (vHPC) mainly modulated the effects of nicotine on contextual fear extinction (Kutlu et al 2016b), we investigated these two sub-regions separately.…”
Section: Introductionmentioning
confidence: 99%